Verrucous Carcinoma of the Vulva: A Case Report and Review of the Literature - Bouquet de Jolinière, Jean; Khomsi, F.; Gothuey, J. M.; Guillou, L.; Fadhlaoui, A.; Dubuisson, J. B.; Feki, A. (Frontiers in Surgery, 2016)
Verrucous carcinoma of the vulva is a rare lesion (1). Affecting essentially postmenopausal women, this lesion is a distinct and particular entity in the vulva carcinoma classification and its scalability is uncertain and unpredictable. We present a case concerning a 48-year-old patient, without following after a condyloma acuminate of the vulva (large left lip). The origin of this case will be discussed in this article. The treatment decided was only surgical. A review of literature shows the scarcity of this lesion of the female genital tract.